Mosquito Behavior of Mansonia and Anopheles and Its Relationship With the Filariasis Disease in Taniwel Timur District and Taniwel, Seram barat regency - Johanis F Rehena; Muhammad Nur Matdoan (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
Mansonia mosquitoes are in endemic forest and swamp areas, dirty environments and unused fish farming areas, Mansonia mosquitoes are aggressive and suck blood when humans are at night, outside the home. Anopheles actively seeks blood during illness and at night. This research uses survey and cross sectional research, it discusses to study mosquitoes, the density of mosquitoes mansonia and anopheles, as well as looking at the development of disease (prevalence) of filariasis. The population in this study is the population and population of mosquito mansonia and anopheles in East Taniwel and Taniwel Districts. Filariasis in Taniwel and East Taniwel Sub-districts, West Seram District was reported in local health centers of around 15 people. The outbreak of filariasis in Taniwel District around 2010-2019. Mansonia bleeds people at home when sick at 18: 00-18: 45. While outside the house at night 20: 00-20: 45. While Anopheles mosquitoes bite humans, at dusk and at night at 16.00-24.00, The peak is 02.00-03.00. The density of mansonia mosquitoes in Sohuwe Village, 4.00 - 5.85, Lumalatal 5.00 - 6.60 and Maloang 4.00-5.50 (moderate), Anopheles in Sohuwe 7.00-9.85, Lumalatal 5.89- 6.82, Maloang 5.00-6.50 (high). The prevalence of filariasis in Sohuwe 0.66, Lumlat 0.88. and Maloang 1.54. There is a relationship between attitudes and community relations with filariasis